Tracking Errors of Exchange Traded Funds in Bursa Malaysia - Ku, Alfred Alfred Ing-Soon; Liew, Venus Khim-Sen; Puah, Chin Hong (Macrothink Institute, Inc., 2019)
This study measures the tracking errors of exchange traded funds (ETFs) listed in Bursa Malaysia. Five measures of tracking errors are estimated in this study for the seven ETFs involved. Overall, the best ETF is METFAPA with the least tracking error. The ranking of the remainder ETFs, in the ascending order of tracking error is MYETFID, METFSID, MYETFDJ, CIMC50, FBMKLCI-EA and CIMBA40 (highest tracking error). The findings in this study is expected to provide clue for passive institutional and retail investors on their selection of ETFs to mimic the portfolio of the desired underlying assets. Moreover, it is anticipated that these findings will motivate the improvement in the tracking ability of the existing ETFs, solicit more follow up studies to encourage the development of new ETFs and increase the participation of investors.